Enfoques, instituciones y expertos en una disciplina en crecimiento. El caso del XVI Congreso Panamericano de Educación Física, Ecuador 1997 (Investigaciones) - Scharagrodsky, Pablo Ariel (2022)
From a socio-historical approach emphasizing the social history of knowledge and experts, the following work analyzes the XVI Pan American Congress of Physical Education held in Ecuador in 1997. To carry out the hermeneutical analysis, within the framework of a qualitative methodology, interpretive attention has been focused on various documentary sources, such as proceedings and reports of the congress, the major exhibitions, the general lectures, and the memories related to other Pan American congresses. Likewise, a set of semi-structured interviews have been carried out. Among the conclusions, the congress is identified as a space where the academic community questioned the educational discipline from three major epistemological approaches with important pedagogical-political consequences.